BIOSORPSI LOGAM BERAT Cr(VI) MENGGUNAKAN BAKTERI Streptococcus mutans - Rida Awliyani; Rudi Kartika; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
The research about the biosorpsion of hexavalent chromium heavy metal [Cr(VI)] with Streptococcus mutans bacteria has been carried out. Biosorption has been done by exposure of chromium to broth culture, the consentration and optimum time happened on the 4 day with the biosorption percentage of Cr(VI) by Streptococcus mutans bacteria was obtained at a concentration of Cr(VI) 5 ppm, with a percentage of 90.80%. It shows Streptococcus mutans has potential as biosorbent of Cr(VI). Keywords: Biosorption, Cr(VI), Streptococcus mutans